Evaluating the Impact of Classroom Education on the Management of Septic Shock Using Human Patient Simulation. Issue 1 (February 2016) - Lighthall, Geoffrey K.; Bahmani, Dona; Gaba, David
Abstract : Background: Classroom lectures are the mainstay of imparting knowledge in a structured manner and have the additional goals of stimulating critical thinking, lifelong learning, and improvements in patient care. The impact of lectures on patient care is difficult to examine in critical care because of the heterogeneity in patient conditions and personnel as well as confounders such as time pressure, interruptions, fatigue, and nonstandardized observation methods. Methods: The critical care environment was recreated in a simulation laboratory using a high-fidelity mannequin simulator, where a mannequin simulator with a standardized script for septic shock was presented to trainees. The reproducibility of this patient and associated conditions allowed the evaluation of "clinical performance" in the management of septic shock. In a previous study, we developed and validated tools for the quantitative analysis of house staff managing septic shock simulations. In the present analysis, we examined whether measures of clinical performance were improved in those cases where a lecture on the management of shock preceded a simulated exercise on the management of septic shock. The administration of the septic shock simulations allowed for performance measurements to be calculated for both medical interns and for subsequent management by a larger resident-led team. Results: The analysis revealed that receiving a lecture on shock before managing a simulated patient with septic shock did not produce scores higher than for those who did not receive the previous lecture. This result was similar for both interns managing the patient and for subsequent management by a resident-led team. Conclusions: We failed to find an immediate impact on clinical performance in simulations of septic shock after a lecture on the management of this syndrome. Lectures are likely not a reliable sole method for improving clinical performance in the management of complex disease processes.